ANALISIS EFEKTIVITAS DAN EFISIENSI PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) (Studi Pada Satuan Pendidikan Dasar di Distrik Demta Kabupaten Jayapura) - Agarita Clara Womsiwor; Siti Rofingatun; Theo Allolayuk (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2020)
This research aims to determine and analyze the effectiveness and efficiency of the management of school operational assistance (BOS) in the unit of primary education in the Demta district in 2017- 2018. The type of research used in this research is a type of quantitative research with the buzz using descriptive analysis. Data collection techniques are conducted by spreading questionnaires, documentation, and literature research. This research data is the result of observations in the field,through the dissemination of questionnaires and presentation of data scientifically is a report of the realization of the budget of income and the school spending in the district of Demta. The data was obtained from SD YPK Muris as one of the schools that became samples of research. The theory used to know and analyze the effectiveness and efficiency of fund management of School Operational Assistance (BOS) is the analysis and calculation of the level of effectiveness and efficiency. Based on the results showed that the level or criteria of the effectiveness of the BOS Funds Management in basic education unit in the district Demta said to be in the criteria is very effective in2017 and the year 2018 is said to be ineffective. In the management of the School Operational Assistance (BOS) as a whole is said to be efficient enough in 2017 and 2018 BOS funds managementhas been said to be efficient.